Fruit Morphology and Nutritional Composition of Different Genome Groups of Six Bananas Cultivars from Bali Island - I Nyoman Rai; Ni Nyoman Ari Mayadewi; I Wayan Wiraatmaja; Ni Komang Alit Astiari (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Bali is home to at least 43 banana cultivars, each serving a wide range of purposes. To support its future development, there is a need to obtain essential information on the morphological and nutritional characteristics of these bananas for domestic needs and the tourism market. Therefore, this study aimed to analyze the fruit morphology and nutritional composition of six local Balinese banana cultivars mainly consumed on Bali Island, namely Pisang Mas (AA), Buluh (AAA), Lumut (AAA), Susu (AAB), Raja (ABB) and Kepok (ABB) genomes. The observation of fruit morphology followed the guidelines of the International Plant Genetic Resources Institute method for bananas. The nutritional composition was analyzed using standard methods by measuring the proximate composition, vitamin C and concentrations of minerals K, Ca, Fe and P. Based on the morphological relationship coefficient values, it was discovered that all banana cultivars were closely related. Dessert bananas of Pisang Mas, Buluh, Lumut and Susu shared a close relationship with their ancestor Musa acuminata, which contributed to the ‘A’ genome. Meanwhile, Pisang Raja, which could be employed as a dessert or cooking banana, and Pisang Kepok as a cooking banana, exhibited a closer relationship. Various cultivars showed different nutritional compositions in their fruits. In every 100 g of edible portion, the nutrient values of the six bananas contained high carbohydrates and total energy, abundant vitamin C and K, moderate total fibers and protein, as well as low fat and Fe. Based on the nutritional composition, six Bali banana cultivars were found suitable as valuable ingredients in alleviating food insecurity or as dietary components.